Financial Intermediation Functions of Microfinance Banks in Nigeria: A Vector Autoregressive and Multivariate Approach - Simon, Ekpete, Marshall; Marshal, Iwedi (International Journal of Economics and Financial Modelling, 2017)
This study portrays the financial intermediation functions of microfinance banks in Nigeria from 1992-2014, econometrically it measures the relationship between the total funds mobilized by MFBS and the allocation of funds to deficits sectors of the economy. In analyzing the data, the researchers applied vector autoregressive and multivariate econometrics tools. The result of the analysis of the correlation showed a clear indication of a weak relationship between the ratio of loans and advances to GDP, ratio of total fund mobilized to GDP, as against the negative nexus between the ratio of total investments to GDP. Furthermore the result shows no evidence of long run equilibrium relationship between the variables under study. The causality test reveals the presence of a unidirectional causality running from RGDP to microfinance bank intermediation variables. Finally, the study recommends that there need to deepen the capacity building strides of NDIC by include both staff and directors of microfinance banks to help bridge the skills gap, the government should provide the infrastructure needed such as power and telecommunications to boost financial inclusion, because technology drives financial innovation, multilateral and bilateral funds be sourced to support the development of microfinance sector, the regulation of microfinance banks in Nigeria be strengthened.